(untitled) (Journal of Global Arts Studies, 2024)
Background: This study is set against the backdrop of the national strategy for the digitalization of culture, focusing on the revitalization of intangible cultural heritage (ICH). It analyzes the prospects and methods of applying virtual imaging technology to the intangible cultural heritage of the Li ethnic group in Hainan. Objective: By examining the current state of digital applications for the intangible cultural heritage of the Hainan Li ethnic group, this study aims to identify methods for constructing a virtual imaging platform for the Li ethnic group’s ICH and to explore digital pathways for its dynamic transmission. Methods: The analysis begins with a review and survey of the current digital applications of the Li ethnic group’s ICH, supported by case studies that demonstrate the advantages of virtual imaging technology. The study then presents a personal analysis of the methods and strategies for constructing a virtual reality platform for the Li ethnic group’s ICH, including a detailed development flowchart. Results: The research on the virtual imaging platform and digital transmission pathways for the Hainan Li ethnic group’s ICH suggests that using virtual imaging technology to preserve this heritage is feasible and can produce synergistic outcomes where the whole is greater than the sum of its parts ("1+1>2"). Conclusion: Leveraging virtual imaging technology and combining it with a focus on "digitalization" and "ICH," this study promotes the creative transformation and innovative development of the Li ethnic group’s ICH. This approach has significant national and contemporary relevance for the active preservation and development of the Li ethnic group’s intangible cultural heritage in Hainan.